KKJELL NILLSSON, STEPHAN PAULEIT, SIMON BELL, CARMEN AALBERS Y THOMAS SICK NIELSEN (EDS.) - Peri-urban futures. Scenarios and models for land use change in Europe - de la Cal, Pablo (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2024)
KJELL NILLSSON, STEPHAN PAULEIT, SIMON BELL, CARMEN AALBERS, THOMAS SICK NIELSEN (eds.) Peri-urban futures: Scenarios and models for land use change in Europe Springer, Berlín-Heidelberg, 2013, 453 pp. Tapa dura, 117,69 € Idioma: inglés ISBN: 978-3-642-30528-3 DOI: 10.1007/978-3-642-30529-0